Private life of Poles in the 19th century. “Margins” – introduction (Marginesy, 2021)
“Margins” is the subtitle of the fourth volume of the publishing series “Private life of Poles in the 19th century”. The volumes published so far focused on the issues of privacy and everyday life of Polish women and Poles, seen through the prism of their roles in society and family, and the phenomenon of fashion, taking into account the private life perspective of the authors of the collection of letters, revealing the private side of the careers of Polish women and Poles. The term “Margins” in the subtitle of the volume was used in a double sense – on the one hand, it includes social circles and non‑elite individuals. The notion of “margin” covers areas of the social tissue that are “absent” or neglected and overlooked in Polish historiography. The term was also used in relation to phenomena that researchers undertook sporadically. The articles and dissertations in this volume are intended by the editors to supplement the picture of the private life of Poles in the nineteenth century, rehabilitate neglected and neglected heroes, and give voice to actors left on the margins of research and on the margins of Polish society during the partitions.